1995
DOI: 10.1128/jb.177.22.6560-6567.1995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of translation initiation on Escherichia coli gnd mRNA by formation of a long-range secondary structure involving the ribosome binding site and the internal complementary sequence

Abstract: Previous research has indicated that the growth rate-dependent regulation of Escherichia coli gnd expression involves the internal complementary sequence (ICS), a negative control site that lies within the 6-phosphogluconate dehydrogenase coding sequence. To determine whether the ICS acts as a transcriptional operator or attenuator, we measured ␤-galactosidase-specific activities in strains carrying gnd-lac operon and protein fusions containing or lacking the ICS. Whereas the presence of the ICS repressed ␤-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Silver, 1992a;Ji et al, 1994), whereas the activity of the Gram-negative ArsC protein from the E. coli plasmid R773 ars operon requires glutathione and glutathione reductase . Secondary structures involving the SD sequence and internal complementary sequences inhibit transla tion initiation (Chang et aL., 1995), and predictions of the P. aeruginosa chromosomal ars mRNA in the intergenic region between the arsB and arsC cistrons show a potential secondary structure (Fig. 5) involving both the putative SD sequence and the initiation codon of ArsC.…”
Section: Discussionmentioning
confidence: 92%
“…Silver, 1992a;Ji et al, 1994), whereas the activity of the Gram-negative ArsC protein from the E. coli plasmid R773 ars operon requires glutathione and glutathione reductase . Secondary structures involving the SD sequence and internal complementary sequences inhibit transla tion initiation (Chang et aL., 1995), and predictions of the P. aeruginosa chromosomal ars mRNA in the intergenic region between the arsB and arsC cistrons show a potential secondary structure (Fig. 5) involving both the putative SD sequence and the initiation codon of ArsC.…”
Section: Discussionmentioning
confidence: 92%
“…The regulatory element was thus not a protein encoded by one of these ORFs. We suggest that the 5′ half of the igs may control the uncoupling between transcription of CNF1 from its promoter and translation of the toxin gene required for an efficient fbi mechanism (Carter‐Muenchau and Wolf, 1989; Chang et al ., 1995), for instance in regulating the isomerization step of the transcription (McClure, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was recently shown that expression of the E. coli gnd gene is regulated at the translational level by a long range interaction between the gnd ribosome binding site and an internal complementary sequence lying between codons 71 and 74 of the gnd mRNA. Again, it does not appear that a protein factor is involved in this long range interaction (11). Another interesting translational control mechanism was identified for the bacteriophage Mu mom gene.…”
Section: Discussionmentioning
confidence: 99%